A Comprehensive Approach to Minimize Inventory Costs Using Reliability Centered Maintenance, Reliability Centered Spares, and Economic Order Quantity Methods - Trismawati; Sabrina Annisa Rizky; Dwi Iryaning Handayani (Journal of Development Research, 2024)
This research aims to optimize the management of spare parts inventory by considering the level of component damage. To achieve this goal, Reliability Centered Maintenance (RCM), Reliability Centered Spares (RCS), and Economic Order Quantity (EOQ) methods are used. Based on the research results, maintenance intervals were found for each component calculated using the RCM method, and the required amount of spares for one repair period was calculated using the RCS method. The research also calculated the EOQ to determine each component's reorder point, safety stock, optimal order quantity, and total cost. The EOQ calculation results were compared with the total cost before the calculation, and it was found that by using the integration of RCM, RCS, and EOQ, the company can minimize costs of Rp. 2,390,119,- for the 5 analyzed components. Therefore, it can be concluded that the use of RCM, RCS, and EOQ methods can help companies optimize spare part inventory management.